Bridging Technology and Pedagogy: Demographics as a Lens to Understand TPACK Utilization Among Primary School Teachers - Setiawan, Heri; Efendi, Anwar; Prasetyo, Iis; Maulyda, Mohammad Archi (Pedagogika, 2025)
The purpose of this study is to analyzing the relationship between teacher demographics and TPACK utilization. The data analysis using several statistical techniques included descriptive analysis, normality tests, correlation analyses, linear regression, and univariate analysis. The research results show that demographic variables such as age and geographic location have a significant impact on elementary teachers’ TPACK, but gender and educational background do not have a significant influence.